2019
DOI: 10.5588/pha.18.0071
|View full text |Cite
|
Sign up to set email alerts
|

Successful implementation of bedaquiline for multidrug-resistant TB treatment in remote Papua New Guinea

Abstract: Setting: Bedaquiline (BDQ) was introduced in the multidrug-resistant tuberculosis (MDR-TB) programme in Daru in remote Papua New Guinea in 2015, along with a core package of active drug-safety monitoring (aDSM). Objective: To assess interim results and safety of BDQ for the treatment of MDR-TB from 1 July 2015 to 31 December 2017. Design: A retrospective cohort analysis of routine programme data. Results: Of 277 MDR-TB patients, 77 (39%) received BDQ with a total of 8 serious adverse events including 5 (6.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Taune, M., et al conducted a retrospective cohort to describe the implementation of bedaquiline and assess the safety and interim effectiveness for MDR-TB patients commenced on bedaquiline, their results found that bedaquiline is a safe and feasible drug with good interim effectiveness [20]. Studies based on children and adolescents with DR-TB also show that bedaquiline containing regimens are effective and well tolerated in children and adolescents, which may provide new ideas for tuberculosis treatment in this group and contribute to the global strategy to end tuberculosis [20][21][22]. However, we did not evaluate the e cacy of bedaquiline in the treatment of children and adolescent patients with DR-TB, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taune, M., et al conducted a retrospective cohort to describe the implementation of bedaquiline and assess the safety and interim effectiveness for MDR-TB patients commenced on bedaquiline, their results found that bedaquiline is a safe and feasible drug with good interim effectiveness [20]. Studies based on children and adolescents with DR-TB also show that bedaquiline containing regimens are effective and well tolerated in children and adolescents, which may provide new ideas for tuberculosis treatment in this group and contribute to the global strategy to end tuberculosis [20][21][22]. However, we did not evaluate the e cacy of bedaquiline in the treatment of children and adolescent patients with DR-TB, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…There are many adverse reactions in the use of bedaquiline, such as hyperuricaemia, nausea, arthralgia, liver injury and QT prolongation and so on [18][19][20][21][22][23][24]. Guglielmetti, L., et al found nearly 20% patients experienced a > = 60-ms increase in QT interval, and leading to bedaquiline discontinuation in 6% patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were a number of concurrent interventions across this time period, we believe that this service has contributed, in part, to the very good outcomes now seen for MDR-TB patients in Daru (20, 21). Treatment success rates for the 2015 MDR TB enrolment cohort were 81%, with only 4% of patients being lost to follow up and 4% failing treatment (20).…”
Section: Current Role and Global Experience With Telemedicine In Mdr-mentioning
confidence: 95%
“…This led to the establishment of the emergency response task force for MDR-TB in 2014, led by the National Department of Health in PNG with support from the Australian Government, across three identified “hotspot” provinces, including Daru, Western Province. The programmatic interventions during the response in Daru 2014-17 and clinical care model have been described elsewhere (20, 21).…”
Section: Current Role and Global Experience With Telemedicine In Mdr-mentioning
confidence: 99%
See 1 more Smart Citation